Nudity as Punishment: Problems of Physicality in the Penitentiary Sphere - Maxim V. Pulkin (Corpus Mundi, 2025)
The article examines the problems of combining various types of punishment and nudity from a historical perspective. The study is based on a combination of historical-genetic and comparative methods, designed to collectively compare the specific features of punishment by exposure in different historical eras. The word “penal” in the title of the article is used in the broadest sense, as “related to punishment”, not always and not necessarily sanctioned by the state. The study revealed that in a significant number of cases, nudity for the purpose of punishment was additional retribution for misconduct, which could be combined with other, much more cruel forms of physical force. The gradual growth of the humanizing influence of Christianity did not stop the use of nudity as a method of punishment for sins. However, nudity gradually ceases to be combined with other, more severe types of punishment, turning into an independent way of preventing various forms of deviant behavior, including adultery. Social upheavals of the early twentieth century revived the ancient meaning of nudity, which, combined with brutal torture and massacres, again becomes a way of fighting class enemies and representatives of hostile states. The article is intended for historians, psychologists, religious scholars.